Inside Back Cover: A Carbonic Anhydrase IX (CAIX)‐Anchored Rhenium(I) Photosensitizer Evokes Pyroptosis for Enhanced Anti‐Tumor Immunity (Angew. Chem. Int. Ed. 8/2022). Issue 8 (28th January 2022) - Su, Xuxian; Wang, Wen‐Jin; Cao, Qian; Zhang, Hang; Liu, Bin; Ling, Yuyi; Zhou, Xiaotong; Mao, Zong‐Wan
Abstract : Pyroptosis is a unique form of programmed cell death that is essentially proinflammatory and critical for immunity. In their Research Article(e202115800), Qian Cao, Zong‐Wan Mao, and co‐workers developed a carbonic anhydrase IX (CAIX)‐anchored photosensitizer, CA‐Re, that is capable of inducing and self‐reporting membrane rupture upon irradiation, as well as evoking pyroptosis to activate antitumor immunity. CA‐Re is the first metal‐complex‐based pyroptosis inducer, and this work provides a promising avenue for cancer metalloimmunotherapy.